Targeting Aberrantly Elevated Sialyl Lewis A as a Potential Therapy for Impaired Endometrial Selection Ability in Unexplained Recurrent Miscarriage - Ma, Zhi; Yang, Huixia; Kessler, Mirjana; Sperandio, Markus; Mahner, Sven; Jeschke, Udo; von Schönfeldt, Viktoria (Frontiers in Immunology, 2022)
Carbohydrate Lewis antigens including sialyl Lewis A (sLeA), sialyl Lewis X (sLeX), Lewis X (LeX), and Lewis Y (LeY) are the commonest cell surface glycoconjugates that play pivotal roles in multiple biological processes, including cell adhesion and cell communication events during embryogenesis. SLeX, LeY, and associated glycosyltransferases ST3GAL3 and FUT4 have been reported to be involved in human embryo implantation. While the expression pattern of Lewis antigens in the decidua of unexplained recurrent miscarriage (uRM) patients remains unclear. Paraffin-embedded placental tissue slides collected from patients experiencing early miscarriages (6–12 weeks) were analyzed using immunohistochemical (IHC) staining. An in vitro assay was developed using endometrial cell line RL95-2 and trophoblast cell line HTR-8/SVneo. HTR-8/SVneo cells spheroids adhesion assay was applied to investigate the intrinsic role of Lewis antigens in the abnormal implantation process of uRM. The expression of Lewis antigens in RL95-2 cells in response to the treatment with pro-implantation cytokine IL-1β were further measured by flow cytometry and immunocytochemical (ICC) staining. IHC staining revealed that Lewis antigens are mainly expressed in the luminal and glandular epithelium, FUTs, ST3GALs, and NEU1 located in both stromal and epithelial cells. We have found that expression of sLeA, LeX, FUT3/4, and ST3GAL3/4 are significantly upregulated in the RM group, while FUT1 is downregulated. SLeX, LeY, ST3GAL6, and NEU1 showed no significant differences between groups. Anti-sLeA antibody can remarkably suppress both the basal and IL-1β induced adhesion of HTR-8/SVneo spheroids to RL95-2 cells monolayer. While further flow cytometry and ICC detection indicated that the treatment of RL95-2 cells with IL-1β significantly increases the surface expression of LeX, but not sLeA. SLeA, LeX, and pertinent glycosyltransferase genes FUT1/3/4 and ST3GAL3/4 are notably dysregulated in the decidua of uRM patients. Targeting aberrantly elevated sLeA may be potential therapy for the inappropriate implantation in uRM.